On the two flow states in the wake of a hatchback Ahmed body. Issue 173 (February 2018) - Rao, A.; Minelli, G.; Basara, B.; Krajnović, S.
Abstract: Recent experimental investigations in the wake of an idealised car model – the Ahmed body showed the existence of two stable wake states: flow state I, where the flow is fully separated over the back slant of the Ahmed body, and flow state II, where the flow initially separates and then reattaches further along the back slant. The existence of the two flow states is confirmed numerically by using the partially-averaged Navier–Stokes (PANS) turbulence model for various configurations of the Ahmed body. The two flow states can also be distinguished by the instantaneous values of the force coefficients. In flow state I, values of both the lift and drag coefficient are lower compared to flow state II. The influence of the aspect ratio, defined as the ratio of the width of the model to that of a standard Ahmed body, on the two flow states is investigated for the 25 ° back slant Ahmed body. For low aspect ratios, flow state II is observed, while for larger aspect ratios, flow state I is observed. Next, the influence of the yaw angle ( β ) on the occurrence of the two flow states is investigated for the 35 ° back slant Ahmed body. For | β | ≲ 12.5 °, flow state I is observed; and as the yaw angle is increased to | β | = 15 °, flow state II is observed, with stronger longitudinal vortices aiding the flow reattachment over the back slant.